2000
DOI: 10.1046/j.1365-2958.2000.01973.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional roles of conserved amino acid residues surrounding the phosphorylatable histidine of the yeast phosphorelay protein YPD1

Abstract: SummaryThe histidine-containing phosphotransfer (HPt) protein YPD1 is an osmoregulatory protein in yeast that facilitates phosphoryl transfer between the two response regulator domains associated with SLN1 and SSK1. Based on the crystal structure of YPD1 and the sequence alignment of YPD1 with other HPt domains, we site-specifically engineered and purified several YPD1 mutants in order to examine the role of conserved residues surrounding the phosphorylatable histidine (H64). Substitution of the positively cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 28 publications
3
49
0
2
Order By: Relevance
“…Surprisingly, however, mutagenesis of the corresponding residues in Ypd1 (K67A and Q86A) seems to have little effect on the ability to transfer phosphoryl groups to and from response regulator proteins (40). Similar results have been obtained with the corresponding Gln3 Ala mutation in ArcB C (41).…”
Section: Mutations Of Conserved Hpt Residues Block the Atp-dependent supporting
confidence: 67%
“…Surprisingly, however, mutagenesis of the corresponding residues in Ypd1 (K67A and Q86A) seems to have little effect on the ability to transfer phosphoryl groups to and from response regulator proteins (40). Similar results have been obtained with the corresponding Gln3 Ala mutation in ArcB C (41).…”
Section: Mutations Of Conserved Hpt Residues Block the Atp-dependent supporting
confidence: 67%
“…Subsequently, the phosphate group is transferred to His64 on Ypd1p and further to Asp554 on Ssk1p. This sequence of events has been demonstrated convincingly by analysis of truncated and mutated proteins both in vivo and in vitro (256)(257)(258)476). These studies also demonstrate that in vivo the histidine kinase cannot bypass the Sln1p response regulator.…”
Section: Hog Map Kinase Pathway In S Cerevisiaementioning
confidence: 64%
“…Transfer from Sln1p His576 to Asp1144 was reported to be unidirectional, while that from Sln1p Asp1144 to Ypd1p His64 was reversible. The entire reaction is, however, driven towards phosphorylation of Ssk1p, since the equilibrium of the reaction from Ypd1p His64 to Ssk1p Asp554 was on the side of the latter (256)(257)(258). It was observed that Ypd1p has a significant stabilizing effect on phospho-Ssk1p; this effect is much less pronounced with a mutant version of Ypd1p that cannot be phosphorylated (256).…”
Section: Hog Map Kinase Pathway In S Cerevisiaementioning
confidence: 99%
“…Comparison of residues predicted to be at the Hpt/ ChpArec interface based on the Rhodobacter sphaeroides CheA2 Hpt-CheY6 complex crystal structure Protein Data Bank code 3KYJ (41) reveals that Hpt1 does not share any of the four predicted interface residues located on the ␣A helix of Hpt2-6, including a conserved Phe, and only three out of the six residues on the ␣B helix (data not shown), consistent with the possibility that Hpt1 has diminished affinity for ChpArec. Additionally, the Lys at position H ϩ 3 that is found in Hpt2-6 and is missing from Hpt1 is required for efficient phosphorylation of the YPD1 Hpt protein by partner and non-partner receiver domains (42). Similarly, the absence in Hpt1 of an Arg at position H Ϫ 3 that is present in Hpt2-6 may contribute to the diminished reactivity of Hpt1 (32).…”
Section: Discussionmentioning
confidence: 99%